The rhythm of memory. Does theta frequency audio/visual flicker improve recall? - Simeonov, Louise; Das, Ravi (Frontiers in Behavioral Neuroscience, 2025)
A fundamental question in cognitive neuroscience is how multi-sensory elements are bound into a unified memory trace. The formation of memories is thought to be reliant on precisely timed neural activity. Theta frequency neural oscillations have been proposed to orchestrate the timing of different sensory cortices. Here, we attempt to replicate findings that flickering stimuli presented in synchronous theta frequency will lead to enhanced recall. Additionally, we investigate whether theta frequency sensory flicker can improve encoding of emotional associative memories. The current study failed to replicate previous findings demonstrating improved recall for stimuli synchronously modulated at theta frequency in a multi-sensory associative learning task. We discuss possible explanations for the discrepancy between current and previous findings.